Mercury abatement in the environment: Insights from industrial emissions and fates in the environment - Hsin-Chieh Kung; Chien-Hsing Wu; Bo-Wun Huang; Guo-Ping Chang-Chien; Justus Kavita Mutuku; Wan-Ching Lin (Heliyon, 2024)
Mercury's neurotoxic effects have prompted the development of advanced control and remediation methods to meet stringent measures for industries with high-mercury feedstocks. Industries with significant Hg emissions, including artisanal and small-scale gold mining (ASGM)-789.2 Mg year−1, coal combustion-564.1 Mg year−1, waste combustion-316.1 Mg year−1, cement production-224.5 Mg year−1, and non-ferrous metals smelting-204.1 Mg year−1, use oxidants and adsorbents capture Hg from waste streams. Oxidizing agents such as O3, Cl2, HCl, CaBr2, CaCl2, and NH4Cl oxidize Hg0 to Hg2+ for easier adsorption. To functionalize adsorbents, carbonaceous ones use S, SO2, and Na2S, metal-based adsorbents use dimercaprol, and polymer-based adsorbents are grafted with acrylonitrile and hydroxylamine hydrochloride. Adsorption capacities span 0.2–85.6 mg g−1 for carbonaceous, 0.5–14.8 mg g−1 for metal-based, and 168.1–1216 mg g−1 for polymer-based adsorbents. Assessing Hg contamination in soils and sediments uses bioindicators and stable isotopes. Remediation approaches include heat treatment, chemical stabilization and immobilization, and phytoremediation techniques when contamination exceeds thresholds. Achieving a substantially Hg-free ecosystem remains a formidable challenge, chiefly due to the ASGM industry, policy gaps, and Hg persistence. Nevertheless, improvements in adsorbent technologies hold potential.